Uso das histórias em quadrinhos no ensino de frações no sexto ano do ensino fundamenta - Silva, Adriani Cilene (2022)
This dissertation, allocated in the line of research Educational practices in Science and Mathematics teaching, sought to investigate the potential that a teaching proposal, based on the use of comics, thus sought to analyze whether the use of comics creates opportunities for Appendization, which analyzed the transcription of scientific concepts for spontaneous ones. It is a qualitative research, theoretically based on some of Vygotsky's ideas, among them, the creation of scientific and spontaneous concepts. A didactic sequence was developed and applied, supported by the Didactic Engineering research methodology. The work was developed in two classes of sixth year of Elementary School, from two municipal schools - in the city of Tapejara/RS. The didactic sequence resulting from this study generated a Guide for fractions classes with the use of comics for teachers who wish to use them in their classrooms, which is associated with this dissertation. To analyze whether the objectives were achieved, we used class diaries, both by the teacher/researcher and by the students, in addition to an initial and final questionnaire – answered by the students – and an analysis of the material produced by them. The data collected and analyzed point to the relevance of working with the use of comics in teaching the content of fractions in Elementary School, as well as pointing out that this potential activity is in helping students to interpret and understand this mathematical content in their interactions everyday. The use of comics as a teaching resource in mathematics classes is an interesting resource, as it allows students to build their understanding of the mathematical content learned. However, it is necessary for the teacher to have mastery and knowledge of the resource he is using in the classroom so that he is able to act effectively, practicing a mediation of knowledge. Accompanying the dissertation is the educational product, available at <http://educapes.capes.gov.br/handle/capes/715917>.